Quiet until the thaw [compact disc, unabridged] : a novel - Fuller, Alexandra, 1969- (Books on Tape, an imprint of the Penguin Random House Audio Publishing Group, 2017)
Follows the experiences of two Native American cousins who become estranged by their different approaches to fighting cultural injustice and whose lives are disrupted by prison, parenthood, and violence.